Produção de material didático para EaD nos cursos de Licenciatura em Matemática: o caso da UAB/IFCE - Guedes, Jane de Fontes (2011)
In the context of distance education, the teaching material occupies a central position and thus show up many issues relating to it. Thus, a major problem is around how they are being produced learning materials tailored to the needs and characteristics of the student, regardless of place and time, study and learn by mediating technologies, constituting a relevant research problem in this area. Some questions that guide the research are: How does the process of production of the degree in mathematics content, involving the author teacher and teacher’s training, occurs at the content’s preparation? What elements produced in the educational materials for undergraduate in Mathematics promote dialogue with the student? How to establish an objective communication between the production team to make the necessary adjustments to the quality of the material, as well as learning objectives? Based on these questions, this research aimed to investigate the production of the material teaching to distance education using as a case study the undergraduate courses in mathematics at a distance in the context of the Open University of Brazil offered by the Federal Institute of Ceará – IFCE (abbreviation in Portuguese). The research methodology has focused on analysis to identify how teachers are producing digital educational content based on the training received for this purpose, analyze the development and production compared to the relationship between teacher content way versus instructional designer (ID); and make an analysis of previous elements in the order to describe and identify the specificities, limits and potential of the training course. The results were shown in the statements of the individuals in which the training meets the purpose of production of the content of mathematics even if it needs to improve aspects of communication between the content author teacher and the DI, compliance with deadlines, the application of the methodology Contextualized Instructional Design - DIC (abbreviation in Portuguese) and diversification of activity in media content specific to mathematics